Improving water and hand-washing services in rural health care facilities in Kitui County, Kenya - Katuva, J; Hope, R; McBurney, E; Gladstone, N; Nyaga, C; Njung'e, D (University of Oxford, 2022)
This study draws upon a diagnostic survey of WASH in health care facilities in Kitui County, Kenya, in 2019, and a pilot intervention providing professional delivery of water and soap services to 11 rural dispensaries in 2020. Three objectives guide the work. First, to estimate the annualised cost of providing safe water and soap in dispensaries. Second, to understand how these costs vary by location. Third, to chart the relative difference in costs of water from piped water schemes and vended water. The results estimate an annualised cost of water and soap services of around USD 1 per health care facility visit. Costs vary by remoteness and are higher for dispensaries relying on vended water provision rather than piped water schemes. The authors propose that county government include these cost estimates in future budget and investment planning, support professional service delivery models, and exploit synergies to manage water services to schools and communities.